The Design of a Surge Protector for Low Voltage Equipment (Class A) - Amizah, Mohd Ariffen; Abd. Malek; Ismail, Daut; Kamsani, Abdul Majid (Kolej Universiti Kejuruteraan Utara Malaysia, 2008)
Link to publisher's homepage at http://jere.unimap.edu.my